Hemophagocytic Syndrome Secondary to Cytomegalovirus Infection in an Infant - Paul, Subhasish; Guha, Suparna; Basu, Sumita; Mukherjee, Dilip Kumar; Banerjee, Raja (Journal of Nepal Paediatric Society, 2016)
Haemophagocytic syndrome caused by CMV infection in a one month old infant is rare. Cytomegalovirus can cause congenital or perinatal infection in an infant. We report a case in a baby who had secondary haemophagocytic syndrome. The baby had progressive pancytopenia, hepatosplenomegaly and diagnosed to be infected with CMV. Inspite of aggressive management the baby succumbed to death. CMV infection in a neonate may predispose to haemophagocytic syndrome. J Nepal Paediatr Soc 2016;36(1):88-90.